1982
DOI: 10.1007/bf01832847
|View full text |Cite
|
Sign up to set email alerts
|

A predator prey model with age structure

Abstract: Abstract.A general predator-prey model is considered in which the predator population is assumed to have an age structure which significantly affects its fecundity. The model equations are derived from the general McKendrick equations for age structured populations. The existence, stability and destabilization of equilibria are studied as they depend on the prey's natural carrying capacity and the maturation period rn of the predator. The main result of the paper is that for a broad class of maturation functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 13 publications
0
55
0
1
Order By: Relevance
“…We refer to Ruan and Xiao [38] for a detailed presentation of model (1.2) and an overview on this topic. We also refer to Cushing and Saleem [13] for a presentation of prey-predator systems with an age structure.…”
Section: (T)u (T)mentioning
confidence: 99%
“…We refer to Ruan and Xiao [38] for a detailed presentation of model (1.2) and an overview on this topic. We also refer to Cushing and Saleem [13] for a presentation of prey-predator systems with an age structure.…”
Section: (T)u (T)mentioning
confidence: 99%
“…However, it is also increasingly realized that time delays are not necessarily destabilizing (see, e.g., Cushing andSaleem, 1982 andHastings, 1983). Additionally, Saleem et al (1987) confirmed this previous finding by arguing that increasing (decreasing) time delays are not necessarily destabilizing (stabilizing).…”
Section: Delay Effects In Dynamic Logit Modelsmentioning
confidence: 92%
“…We would like to mention that switching of stabilities in delayed predator-prey models has been observed and studied in Cushing [25] and Cushing and Saleem [26].…”
Section: Theorem 22mentioning
confidence: 99%